Inovasi Pemanfaatan Teknologi Digital Oleh Kader Posyandu Untuk Memperkuat Dan Mengembangkan Kesehatan Masyarakat Di Kecamatan Baros Kota Sukabumi - Neneng Yanti Andriani; Tedi Pitri; Sindrawati; Siti Purnamasari (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
Technology provides convenience and efficiency that can optimize the tasks of Posyandu cadres, one of the implementations is digital recording. However, in practice, recording Posyandu activities is still done manually, using register books that take a long time, are prone to errors, and are difficult to analyze quickly. The problems of Posyandu cadres in digital technology in Baros District face obstacles such as lack of digital literacy of cadres, limited devices and internet networks, and the lack of ongoing platform technical training, so that cadres return to manual formats and through G Forms due to the absence of a routine monitoring & evaluation system. A comprehensive approach is needed to optimize the role of cadres through the use of technology to bridge the information gap between cadres and the community through platforms and social media, thereby increasing public awareness of preventive health and encouraging healthy behavior changes. This study aims to improve innovation in the use of digital technology by Posyandu cadres in an effort to strengthen and develop public health. The research method used is a mixed-methods method that is able to examine in depth the effectiveness and obstacles to the use of digital technology by Posyandu cadres. A different approach from other studies This study specifically explores how Posyandu cadres in Baros District utilize digital technology, social media and the SIPOSMI application in health services. This study will contribute to strengthening empirical evidence related to strategies, effectiveness, and perceptions of the use of digital technology in Posyandu services.